1996
DOI: 10.1002/(sici)1099-1573(199608)10:5<379::aid-ptr849>3.3.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemic Effects of Opuntia ficusindica Mill., Opuntia lindheimeri Engelm and Opuntia robusta Wendl. in Streptozotocin‐induced Diabetic Rats

Abstract: The hypoglycaemic activities of Opuntia ficus-indica, 0. lindheimeri and 0. robusta were investigated in streptozotocin-induced diabetic rats using enteral (oral) and parenteral (intraperitoneal and intravenous) routes of administration. When the aqueous extracts of the three Opunfriz species were administred intraveneously, they produced a hypoglycaemic effect. However, when the extracts were administered orally, only 0. lindheimeri produced a hypoglycaemic effect. A dilute aqueous (ammonium sulphate) solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…3; Panel B). These results agree with previous reports which have documented oral administration of Opuntia species to lower blood glucose in diabetic rat and rabbit models (Enigbokan et al, 1996;Ibanez-Camacho et al, 1983). Consistent with the report by Enigbokan et al, the hypoglycaemic effect of O. lindheimeri was apparent within 1 h of administration.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…3; Panel B). These results agree with previous reports which have documented oral administration of Opuntia species to lower blood glucose in diabetic rat and rabbit models (Enigbokan et al, 1996;Ibanez-Camacho et al, 1983). Consistent with the report by Enigbokan et al, the hypoglycaemic effect of O. lindheimeri was apparent within 1 h of administration.…”
Section: Resultssupporting
confidence: 93%
“…The O. lindheimeri used in this study was obtained from a Opuntia planting in a germplasm collection at Texas A&M University-Kingsville. The botanical identity of the plant materials had been previously confirmed through the USDA, National Germplasm Resources Laboratory, Beltsville, Maryland, and the Plant Collection Center, Florida, USA (Enigbokan et al, 1996). Stems (cladodes) were harvested and extracts prepared as described by Ibanez-Camacho et al (1983).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dose of 6 mg/kg for the extract blend was chosen based on the significant effects of aqueous extract on plasma insulin levels, however, so far a dose finding study with the proprietary blend has not been performed. Our results confirm earlier studies where blood sugar lowering effects of Opuntia ficus‐indica extracts (Enigbokan et al ., 1996; Frati‐Munari et al ., 1989) have been reported. It has been suggested in the literature that a decrease in hyperglycemia is only noticed with broiled stems of O. ssp.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in contrast to the results reported by Enigbokan et al . (1996) who demonstrated that extracts from O. lindheimeri were effective as a hypoglycemic agent when administered orally, whereas extracts from Opuntia ficus‐indica were effective only when administered intravenously. The reasons for these discrepancies are not known but it is likely that the effect seems to depend on the applied preparation and extraction method and the parts of the plant that have been used.…”
Section: Discussionmentioning
confidence: 99%